Surface properties in titanium with hydroxyapatite coating - Dudek, Agata (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Due to its wide range of possible applications in current technology, hydroxyapatite, as a biomaterial, has been of great interest to scholars. Improvement in mechanical properties can be achieved by addition of zirconia, partially stabilized by yttrium, into a resistant oxide phase. The present study describes the microstructure and phases which are typical of composite coatings after plasma spraying.
Optica Applicata, Vol. 39, 2009, nr 4, s. 825-831
Keywords: optyka; hydroxyapatite; zirconia; XRD